Precipitating factors and targeted therapies in combating the perils of sickle cell disease— A special nutritional consideration. Issue 1 (December 2016) - Khan, Shahida; Damanhouri, Ghazi; Ali, Ashraf; Khan, Sarah; Khan, Aziz; Bakillah, Ahmed; Marouf, Samy; Al Harbi, Ghazi; Halawani, Saeed; Makki, Ahmad
Abstract Nutritional research in sickle cell disease has been the focus in recent times owing to not only specific nutritional deficiencies, but also the improvements associated with less painful episodes. Though hydroxyurea remains the drug of choice, certain adverse health effects on long term supplementation makes room for researches of different compounds. Macro and micro nutrient deficiencies, along with vitamins, play an important role in not only meeting the calorific needs, but also reducing clinical complications and growth abnormalities. Symptoms of hyper protein metabolism, increased cell turnover, increased cardiac output, and appetite suppression due to enhanced cytokine production, might give us leads for better understanding of the mechanisms involved. Different nutritional approaches comprising of traditional herbal therapies, antioxidants, flavonoids, vitamins, minerals etc., reducing oxidative stress and blood aggregation, have been tried out to increase the health potential. Nutritional therapies may also serve complementary to the newer therapies using ozone, hematopoietic stem cell transplantation, antifungal medications, erythropoietin etc. Herein we try to present a holistic picture of the different patho-physiological mechanisms, and nutritional strategies adopted.